"We Are at Risk Too": The Disparate Mental Health Impacts of the Pandemic on Younger Generations: Nous Sommes Aussi à Risque: Les Effets Disparates de la Pandémie Sur la Santé Mentale des Générations Plus Jeunes. (July 2021) - El-Gabalawy, Renée; Sommer, Jordana L.
Objectives: The coronavirus 2019 (COVID-19) pandemic has resulted in profound global impact, with older adults at greater risk of serious physical health outcomes. It is essential to also understand generational differences in psychosocial impacts to identify appropriate prevention and intervention targets. Across generational groups, this study examined: (1) rates of precautions and adaptive and maladaptive health behaviors, (2) differences in levels of anxiety, and (3) rates of COVID-related concerns during Wave 1 of COVID-19 in Canada. Participants: We analyzed data from 2 Canadian population-based data sets: the Canadian Perspective Survey Series: Impact of COVID-19 survey ( N = 4, 627; March 29 to April 3, 2020), and Crowdsourcing: Impacts of COVID-19 on Canadians—Your Mental Health ( N = 45, 989; April 24 to May 11, 2020). Measures: We categorized generational age group. Participants self-reported changes in behaviors and COVID-related concerns, and a validated measure assessed anxiety symptoms. Results: There are generational differences in behavioral responses to the pandemic. Adaptive health habits (e.g., exercise) were comparable across groups, while changes in maladaptive health habits (e.g., substance use) were highest among younger age groups, particularly Millennials (15 to 34 years old). COVID-related precautions were also highest among the younger generations, with Generation X (35 to 54 years old) exhibiting the highest rate of precautionary behavior. Results also revealed that the highest rate of clinically significant anxiety is among Millennials (36.0%; severe anxiety = 15.7%), and the younger generations have the highest rates of COVID-related concerns. Conclusion: These early data are essential in understanding at-risk groups given the unpredictable nature of the pandemic and its potential long-term implications.